Efektivitas Pembelajaran Direct Intruction Menggunakan Modifikasi Bola Voli Mini Terhadap Hasil Belajar Servis Bawah Dalam Permainan Bola Voli Pada SiswaKelas Atas SD Negeri RanterejoKabupaten Kebumen - Puput Widodo; Irvangi Irvangi (Departement of Mathematics Education, 2024)
The lack of student interest in learning volleyball as well as students' different learning abilities and students' lack of activity in physical education learning carried out in the classroom and on the field means that it is necessary to apply a more effective and innovative direct instruction learning model. The aim of this research is to find out whether there is an effectiveness of the Direct Instruction Learning Model Using Mini Volleyball Modifications on the Learning Outcomes of Lower Service in Volleyball Games in Class IV, V and VI Students at Ranterejo Public Elementary School, Kebumen Regency. The type of research in this research is experimental research with a quantitative descriptive approach. The design used in this research is Pre-Experimental Design (nondesigns). Before the data obtained from the field is analyzed further, it is first tested with a normality test. The results of the t-test show that the calculated t is 13,104 > 2.05 (t-table) and the probability significance value is 0.000 < 0.05, meaning that there is a significant influence from the Direct Instruction learning model using Peching Box on learning outcomes for pencak silat front kicks. in Class Students In Class IV, V and VI Students at SD Negeri Ranterejo, Kebumen Regency. In this study, the pre-test was carried out at the beginning and the post-test at the end. The treatment is given after the pre-test is carried out. Prior to the Direct Instruction Learning Model Using Mini Volleyball Modifications on the Learning Outcomes of Lower Service in Volleyball Games in Class IV, V and VI Students at Ranterejo Public Elementary School, Kebumen Regency, the average (pretest) was 63.57 and at the posttest it increased to 80 .54. It turns out that the average (pretest) after being given the Direct Instruction Learning Model Using Modified Mini Volleyball was 16.97 with an increase percentage of 26.69%. Based on the research results that have been obtained by data analysis and hypothesis testing, it can be concluded that